There is more to perinatal mental health care than depression: Public health nurses reported engagement and competence in perinatal mental health care. Issue 3 (7th December 2017) - Higgins, Agnes; Downes, Carmel; Carroll, Margaret; Gill, Ailish; Monahan, Mark
Abstract : Aims and objectives: To explore public health nurses' engagement, competence and education needs in relation to perinatal mental health care in Ireland. Background: It is estimated that 15%–25% of women will experience a mental health problem during or postpregnancy, either as a new problem or a reoccurrence of a pre‐existing problem. Public health nurses, or their equivalent, are ideally positioned to support women's mental health and improve health outcomes for the woman and baby, yet little is known about their role and engagement with mental health issues, other than with postnatal depression. The objectives of the study were to identify public health nurses' knowledge, skills and current practices in perinatal mental health and establish their education needs. Design: The research used a descriptive design. Method: A total of 186 public health nurses completed an anonymous, online survey, designed by the research team. Results: While public health nurses are positive about their role in supporting women's mental health, they lack the knowledge and skills to address all aspects of mental health, including opening a discussion with women on more sensitive or complex issues, such as trauma and psychosis and providing information to women. Those who received education reported statistically significant higher knowledge and confidence scores than those without. Conclusion: Public health nurses lack the knowledge and skills required to provide comprehensive perinatal mental health care to women. Future education programmes need to move beyond postnatal depression and address the range of mental health problems that may impact on women in the perinatal period. Relevance to clinical practice: Without knowledge and skill among nurses in all aspects of perinatal mental health, women with significant mental health needs may be left to cope alone and lack the necessary prompt evidence‐based interventions and supports.